2021
DOI: 10.1021/acs.analchem.1c01503
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Resolution Fluorescence Detected X-ray Absorption Spectroscopy: An Analytical Method for Selenium Speciation

Abstract: Selenium is in many ways an enigmatic element. It is essential for health but toxic in excess, with the difference between the two doses being narrower than for any other element. Environmentally, selenium is of concern due to its toxicity. As the rarest of the essential elements, its low levels often provide challenges to the analytical chemist. X-ray absorption spectroscopy (XAS) provides a powerful tool for in situ chemical speciation but is severely limited by poor spectroscopic resolution arising from cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Spectra collected in HERFD or TFY from thick samples containing high As concentrations (Table S2) could be impacted by over-absorption (self-absorption) that dampens the amplitude of the XAFS oscillations (Newville, 2014). Over-absorption is a result of the fluorescence emission from the sample, and can be present in HERFD and conventional TFY measurements (Nehzati et al, 2021). Over-absorption corrections could not be made because As concentrations (Table S2) were not measured on the same samples used for XAS measurements.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Spectra collected in HERFD or TFY from thick samples containing high As concentrations (Table S2) could be impacted by over-absorption (self-absorption) that dampens the amplitude of the XAFS oscillations (Newville, 2014). Over-absorption is a result of the fluorescence emission from the sample, and can be present in HERFD and conventional TFY measurements (Nehzati et al, 2021). Over-absorption corrections could not be made because As concentrations (Table S2) were not measured on the same samples used for XAS measurements.…”
Section: Figurementioning
confidence: 99%
“…The spectral resolution of U- (Kvashnina et al, 2013;Leinders et al, 2017;Le Pape et al, 2020), Hg- (Proux et al, 2017), Se- (Bissardon et al, 2019;Nehzati et al, 2021), As-(Le Pape et al, 2018), Au- (Tagirov et al, 2016;Filimonova et al, 2020), and Cu-XANES (Tagirov et al, 2016) in geologically or biologically relevant phases have shown notable improvement with HERFD. The high-resolution spectra improve speciation and enable the more accurate determination of oxidation state in samples with low concentrations and/or complex matrices (Proux et al, 2017).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…These include, but are not limited to, the use of the following: Compound specific isotope measurements of Hg, which generate Hg speciated isotope ratios and differentiate Hg isotopic composition of MeHg from various forms of iHg: ,,,, This technique has proven suitable for identifying MeHg and iHg sources in rice and in human populations that have complex dietary patterns (e.g., rice, freshwater fish, and marine fish) . We expect this technique will enable the quantification of isotope fractionation of iHg and MeHg during different internal processes and further expand the utility of Hg isotopes in studying Hg toxicokinetic processes within populations and across organisms. Advanced techniques in X-ray absorption spectroscopy, namely high-energy resolution fluorescence detection X-ray absorption near-edge structure (HERFD-XANES) spectroscopy, which is capable of identifying and quantifying mixtures of biologically relevant Hg species at subparts-per-million concentration: ,, Similarly, HERFD-XANES spectroscopy was recently shown to have an enhanced resolution of Se species relative to normal-resolution XANES . HERFD-XANES spectroscopy can resolve prominent chemical forms of Hg pertinent to identifying the various reactions involved in the two-step MeHg → HgSe reaction. ,, Future research using these methods will advance the understanding of Hg cycling across the scale of food webs to biomolecules. Molecular and protein-level measurements of Hg and Se and S biomolecules, including targeted mass spectrometry of selenoamino acids and low-molecular weight biomolecules (e.g., selenoneine and cysteine) ,, and hyphenated elemental mass spectrometry speciation, will be essential to addressing scientific needs on the interactions of Hg with Se and S biomolecules.…”
Section: Complementary Tools For Elucidating Mercury Toxicokineticsmentioning
confidence: 99%
“…Advanced techniques in X-ray absorption spectroscopy, namely high-energy resolution fluorescence detection X-ray absorption near-edge structure (HERFD-XANES) spectroscopy, which is capable of identifying and quantifying mixtures of biologically relevant Hg species at subparts-per-million concentration: ,, Similarly, HERFD-XANES spectroscopy was recently shown to have an enhanced resolution of Se species relative to normal-resolution XANES . HERFD-XANES spectroscopy can resolve prominent chemical forms of Hg pertinent to identifying the various reactions involved in the two-step MeHg → HgSe reaction. ,, Future research using these methods will advance the understanding of Hg cycling across the scale of food webs to biomolecules.…”
Section: Complementary Tools For Elucidating Mercury Toxicokineticsmentioning
confidence: 99%